# Answer to Question #41637 in Calculus for law

Question #41637

Differentiate with respect to

x: f(x)=(ax 3 +bx)

x: f(x)=(ax 3 +bx)

Expert's answer

Using the table of derivatives and the rule that the derivative of the sum equals the sum of derivatives we get

f'(x)=(ax^3+bx)'=(ax^3)'+(bx)'=3ax^2+b

f'(x)=(ax^3+bx)'=(ax^3)'+(bx)'=3ax^2+b

Need a fast expert's response?

Submit orderand get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

## Comments

## Leave a comment